Isolation and characterization of the DNA region encoding nodulation functions in Bradyrhizobium japonicum. - Russell, P (1985)
The DNA region encoding early nodulation functions of Bradyrhizobium japonicum 3I1b110 (I110) was isolated by its homology to the functionally similar region from Rhizobium meliloti. Isolation of a number of overlapping recombinant clones from this region allowed the construction of a restriction map of the region. The identified nodulation region of B. japonicum shows homology exclusively to those regions of R. meliloti and Rhizobium leguminosarum DNA known to encode early nodulation functions. The region of homology with these two fast-growing Rhizobium species was narrowed to an 11.7-kilobase segment. A nodulation-defective mutant of Rhizobium fredii USDA 201, strain A05B-2, was isolated and found to be defective in the ability to curl soybean root hairs. Some of the isolated recombinant DNA clones of B. japonicum were found to restore wild-type nodulation function to this mutant. Analysis of the complementation results allows the identification of a 1.8-kilobase region as essential for restoration of Hac function.